Terpaan Promosi Cashback dan Intensitas Komunikasi Peer Group Terhadap Minat Menggunakan OVO - Inayah Setia Azzahra; Djoko Setyabudi; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The increasing development of online transactions has led to various digital wallet service applications currently aiming to provide convenience for users in conducting various payment transactions. This study was conducted with the aim of knowing how much influence OVO cashback promotion and peer group communication intensity had on the interest in using OVO. Competition that occurs between e-wallets at this time makes various companies engaged in digital wallets vying to provide the best innovations for their users. In this case, OVO as one of the most widely known as a digital wallet by society also strives to provide attractive services, features, and promotional offers to encourage people to use their service. The theory used in this study is Cognitive Response and Reference Group with a sampling technique in the form of non-probability sampling, with a total sample of 50 people, male and female, aged 18-35 years, and has been exposed with OVO cashback promotions in the last three months. The results of hypothesis, tested by using a simple linear regression technique show that there is an influence between OVO cashback promotion and the intensity of peer group communication to having an interest in using OVO, with a significance value of 0.000 for both hypothesis, which means it is very significant.